Identification and characterization of orthologs of AtNHX5 and AtNHX6 in Brassica napus - Ford, Brett A.; Ernest, Joanne R.; Gendall, Anthony R. (Frontiers in Plant Science, 2012)
Improving crop species by breeding for salt tolerance or introducing salt tolerant traits is one method of increasing crop yields in saline affected areas. The model plant species Arabidopsis thaliana has been extensively studied and there is substantial information available about the function and importance of many genes and proteins involved in salt tolerance. The identification and characterization of A. thaliana orthologs in species such as Brassica napus (oilseed rape) can prove difficult due to the significant genomic changes that have occurred since their divergence approximately 20 million years ago. The recently released B. rapa genome provides an excellent resource for comparative studies of Arabidopsis and the cultivated Brassica species, and facilitates the identification of Brassica species orthologs which may be of agronomic importance. Sodium hydrogen antiporter (NHX) proteins transport a sodium or potassium ion in exchange for a hydrogen ion in the other direction across a membrane. In A. thaliana there are eight members of the NHX family designated AtNHX1-8 that can be sub-divided into three clades (plasma membrane (PM), intracellular class I (IC-I) and intracellular class II (IC-II)) based on their subcellular localization. In plants, many NHX proteins are primary determinants of salt tolerance and act by transporting Na+ out of the cytosol where it would otherwise accumulate to toxic levels. Significant work has been done analyzing both PM and IC-I clade members role in salt tolerance in a variety of plant species but relatively little analysis has been described for the IC-II clade. Here we describe the identification of B. napus orthologs of AtNHX5 and AtNHX6, using the Brassica rapa genome sequence, macro- and micro-synteny analysis, comparative expression and promoter motif analysis, and highlight the value of these multiple approaches for identifying true orthologs in closely related species with multiple paralogs.